2010
DOI: 10.1021/jp909099a
|View full text |Cite
|
Sign up to set email alerts
|

Tautomeric Equilibrium of Uracil and Thymine in Model Protein−Nucleic Acid Contacts. Spectroscopic and Quantum Chemical Approach

Abstract: This work deals with tautomeric transformations of uracil (Ura) and thymine (Thy) in their model complexes with the deprotonated carboxylic group. Essential changes in the UV spectra of the bases upon their interaction with NaAc, vanishing signals of both imino protons in (1)H NMR spectra, and a perceptible decrease in intensity of both IR bands, related to the stretching vibrations nu(C=O) of the carbonyl groups, imply involvement of enolic tautomers. Results of quantum chemical calculations of the double com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…DFT method has been used extensively to search conformational landscape of canonical nucleosides [49][50][51]. However, hybrid method B3LYP evidently affords improved results [52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…DFT method has been used extensively to search conformational landscape of canonical nucleosides [49][50][51]. However, hybrid method B3LYP evidently affords improved results [52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…It is generally believed that Thy exists in the canonical diketo form in the gas phase as well as in the aqueous solution (Kwiatkowski & Pullman, 1975), but there is experimental evidence of small amounts of its rare tautomeric forms in the gas phase (Fujii et al, 1986;Tsuchiya et al, 1988) and in the solution (Hauswirth & Daniels, 1971;Katritzky & Waring, 1962;Morsy et al, 1999;Samijlenko et al, 2010;Suwaiyan et al, 1995). Also laser ablation in combination with MB-FTMW spectroscopy spectroscopy has been used to establish unambiguously the presence of the diketo form of thymine in the gas phase and to obtain its structure (López et al, 2007).…”
Section: Elementary Molecular Mechanisms Of the Spontaneous Point Mutmentioning
confidence: 99%
“…Of particular interest were their interactions with amino acids (Fan et al, 2010;Samijlenko et al, 2001Samijlenko et al, , 2004Stepanyugin et al, 2002aStepanyugin et al, , 2002b and protons or alkali metal cations (Lippert et al, 1986;Lippert & Gupta, 2009;Samijlenko et al, 2010;Šponer et al, 2001), as the extra positive charge could stabilize the structure of rare tautomers through an intramolecular salt bridge. Moreover, the coordination of metal ions to nucleobases is known to lead frequently to the stabilization of rare tautomeric forms (Burda et al, 2000;Lippert et al, 1986;Lippert & Gupta, 2009;Samijlenko et al, 2010), with numerous examples reported for various nucleobases (Lippert & Gupta, 2009;Lippert et al, 1986;Schoellhorn et al, 1989;Renn et al, 1991;Zamora et al, 1997). In these metal-stabilized rare tautomers, the metal is located at a position that is usually occupied by a proton, forcing the proton to move to another position and thereby generating the rare tautomer.…”
Section: Tautomerisation Of the Dna Bases In Dimersmentioning
confidence: 99%
“…Further calculation shows that the interaction between E&E' and Na 2 SO 3 could significantly decrease the conformational energy of the models F&F'. Considering the low compatibility of Na 2 SO 3 and E&E', this result should indicate the existence of the saltesalt interaction between them [37,38]. That said, except the cationeanion interaction and the solvation, the saltesalt interaction should also play a role in stabilizing the [LH] þ cation salt in solution.…”
Section: H Nmr Study Of Tris(2-(dimethylamino)phenyl)methanol Saltsmentioning
confidence: 94%